Transformasi Pelaporan Keuangan Basis Akrual pada Politeknik Keuangan Negara STAN: Sudahkah Tuntas? - Puji Wibowo; Naela Varikha (SUBSTANSI, 2018)
Public Service Agency (BLU) is a special working unit (Satker) which has many flexibilities in terms of revenue and expenditure management. In the light of financial reporting presentation, BLU must comply with PSAP Number 13 which requires single reporting only. Polytechnique of State Finance-STAN (PKN STAN) is one of BLU’s under the Ministry of Finance is not under exemption. This research aims to analyse obstacles and key success faced by PKN STAN in presenting BLU’s financial statement for the budget year 2016 and 2017 by using a qualitative exploratory research. Data were obtained by conducting in-depth interviews with key persons in PKN STAN and regulatory body, literature review, observation, and documentation study. The results show that the presentation of PKN STAN financial statement for the year 2016 was not successfully implemented in terms of PSAP 13 compliance. Meanwhile, PKN STAN succeeded in preparing 2017 financial statement by adopting PSAP 13 and supported by Minister of Finance Regulation Number 220 Year 2016 implementation. Significant issues in those two years that became lessons learned were credible regulation, human resource, integrated system, and communication. It is concluded that integrated system and internal auditor involvement are the most challenge policy in the near future